Paper covers rock - Hubbard, Jenny (New York Delacorte Press, 2011)
In 1982 Buncombe County, North Carolina, sixteen-year-old Alex Stromm writes of the aftermath of the accidental drowning of a friend, as his English teacher reaches out to him while he and a fellow boarding school student try to cover things up
1
Keywords: Boarding schools -- Fiction; Conduct of life -- Fiction; Death -- Fiction; Schools -- Fiction; North Carolina -- History -- 20th century -- Fiction